Exploring the sociotechnical intersection of patient safety and electronic health record implementation. (19th September 2013) - Meeks, Derek W; Takian, Amirhossein; Sittig, Dean F; Singh, Hardeep; Barber, Nick
Abstract: Objective The intersection of electronic health records (EHR) and patient safety is complex. To examine the applicability of two previously developed conceptual models comprehensively to understand safety implications of EHR implementation in the English National Health Service (NHS). Methods We conducted a secondary analysis of interview data from a 30-month longitudinal, prospective, case study-based evaluation of EHR implementation in 12 NHS hospitals. We used a framework analysis approach to apply conceptual models developed by Sittig and Singh to understand better EHR implementation and use: an eight-dimension sociotechnical model and a three-phase patient safety model (safe technology, safe use of technology, and use of technology to improve safety). Results The intersection of patient safety and EHR implementation and use was characterized by risks involving technology (hardware and software, clinical content, and human–computer interfaces), the interaction of technology with non-technological factors, and improper or unsafe use of technology. Our data support that patient safety improvement activities as well as patient safety hazards change as an organization evolves from concerns about safe EHR functionality, ensuring safe and appropriate EHR use, to using the EHR itself to provide ongoing surveillance and monitoring of patient safety. Discussion We demonstrate the face validity of two models for understanding the sociotechnical aspects of safe EHR implementation and the complex interactions of technology within a healthcare system evolving from paper to integrated EHR. Conclusions Using sociotechnical models, including those presented in this paper, may be beneficial to help stakeholders understand, synthesize, and anticipate risks at the intersection of patient safety and health information technology.